Respiratory health of workers exposed to swine confinement buildings only or to both swine confinement buildings and dairy barns. - Cormier, Yvon; Boulet, L. P.; Bedard, G.; Tremblay, G. (Scandinavian Journal of Work, Environment & Health, 1991)
Swine building workers (N = 488) and nonfarming neighborhood referents (N = 216) were enrolled in this study. There was a slight but significant increase in the prevalence of chronic bronchitis (17.49 versus 11.57%) and more evidence of airflow obstruction (forced expiratory volume in 1 s/forced vital capacity 0.75 versus 0.78) among the swine workers when they were compared with the referents. The subjects who spent more than 3 h/d in the swine buildings had a higher prevalence of chronic bronchitis (21.94 versus 13.25%) and airflow obstruction (forced expiratory volume in 1 s/forced vital capacity 0.75 versus 0.76) than those with shorter daily contact. Swine building only workers had no precipitins to antigens found in their environment and no clinical evidence of extrinsic allergic alveolitis. The number of years on the farm, dual exposure with dairy cattle, positive skin prick tests, type of piggery, and type of feeding did not add to the respiratory health impact of swine buildings.